2022
DOI: 10.3389/fnut.2022.896895
|View full text |Cite
|
Sign up to set email alerts
|

University Students' Knowledge and Perceptions About Concepts, Recommendations, and Health Effects of Added Sugars

Abstract: It is recommended to limit added sugars to below 10% of the daily energy intake, as excessive consumption has been associated with several chronic non-communicable diseases. This exploratory qualitative study used focus groups to investigate the knowledge and perception of Brazilian university students about added sugars concepts, consumption recommendations, and health effects. Focus groups were led by a moderator using a semi-structured discussion guide. The focus groups were recorded, transcribed verbatim, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Moreover, egg consumption exceeded 1 portion daily, while the intake of sweets was greater than 5 portions per week. Students may be unaware of the health impacts associated with excessive consumption of added sugar ( 49 ). Likewise, other studies carried out in university students have reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, egg consumption exceeded 1 portion daily, while the intake of sweets was greater than 5 portions per week. Students may be unaware of the health impacts associated with excessive consumption of added sugar ( 49 ). Likewise, other studies carried out in university students have reported similar findings.…”
Section: Discussionmentioning
confidence: 99%